THE LYRICAL NOVEL LORD OF THE FLIES - Costa, Natasha (Revista do SELL, 2014)
The academic researches on the narrative Lord of the Flies, published in 1954 by William Golding, classify it explicit or implicitly as a traditional novel. In this article we intend to show that this work, instead of narrating an individual human experience based on social or cultural terms, focus a mythological and less diffuse subjective experience by using the resources of poetry. In order to study the poetic narrative, or lyrical novel, this research will be founded on the considerations of Jean-Yves Tadié (1978) exposed in Le récit poétique and those of Ralph Freedman (1963) in The lyrical novel. This paper attempts to show that mainly space, time, myth and allegory imprints a poetic form in the essence of the narrative.